Effects of Ranolazine, a Novel Anti-anginal Drug, on Ion Currents and Membrane Potential in Pituitary Tumor GH3 Cells and NG108-15 Neuronal Cells - Bing-Shuo Chen; Yi-Ching Lo; Hsung Peng; Tai-I Hsu; Sheng-Nan Wu (Journal of Pharmacological Sciences, 2009)
Abstract.: Ranolazine, a piperazine derivative, is currently approved for the treatment of chronic angina. However, its ionic mechanisms in other types of cells remain unclear, although it is thought to be a selective blocker of late Na+ current. This study was conducted to evaluate the possible effects of ranolazine on Na+ current (INa), L-type Ca2+ current (ICa,L), inwardly rectifying K+ current (IK(IR)), delayed-rectifier K+ current (IK(DR)), and Ca2+-activated K+ current (IK(Ca)) in pituitary tumor (GH3) cells. Ranolazine depressed the transient and late components of INa with different potencies. This drug exerted an inhibitory effect on IK(IR) with an IC50 value of 0.92 μM, while it slightly inhibited IK(DR) and IK(Ca). It shifted the steady-state activation curve of IK(IR) to more positive potentials with no change in the gating charge of the channel. Ranolazine (30 μM) also reduced the activity of large-conductance Ca2+-activated K+ channels in HEK293T cells expressing α-hSlo. Under current-clamp conditions, low concentrations (e.g., 1 μM) of ranolazine increased the firing of action potentials, while at high concentrations (≥10 μM), it diminished the firing discharge. The exposure to ranolazine also suppressed INa and IK(IR) effectively in NG108-15 neuronal cells. Our study provides evidence that ranolazine could block multiple ion currents such as INa and IK(IR) and suggests that these actions may contribute to some of the functional activities of neurons and endocrine or neuroendocrine cells In vivo. Keywords:: ranolazine, Na+ current, inwardly rectifying K+ current, GH3 cell, NG108-15 cell